The Effect Of Security And Benefits Of Using Digital Wallets (E-Wallets) On Payment Interest In Online Transactions - Tamima, Aqila; Qarni, Waizul; Dharma, Budi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
This study aims to analyze the influence of security and benefits of the use of digital wallets (E-wallets) on payment interest in online transactions among students. This study uses a quantitative approach. The data used in this study is primary data obtained from questionnaires. The sampling technique used in this study is Proportionate Random Sampling. The respondents involved in this study were 87 people. The data analysis used in this study includes multiple regression analysis. The results of the study show that security and benefits have a positive and significant effect on interest in online transactions using digital wallets (E-wallets) in students. The model built was confussed to explain the interest in transactions using digital wallets (E-wallets) by 54.8%. For further research, it is recommended to increase the scope of research and other variables that have an influence on the interest in online payment transactions using digital wallets (E-wallets) so that they are not limited to security and benefit variables only. For E-wallet service providers, they must further increase the benefits of the application so that they can compete with other E-wallet applications. Then security must also be improved because of the rampant cybercrime problem that can harm consumers.